1995
DOI: 10.1007/bf00298434
|View full text |Cite
|
Sign up to set email alerts
|

Enamel matrix protein turnover during amelogenesis: Basic biochemical properties of short-lived sulfated enamel proteins

Abstract: The formation and turnover of sulfated enamel proteins was investigated by SDS-PAGE, fluorography, and TCA-precipitations using freeze-dried incisors of rats injected intravenously with 35S-sulfate (35SO4) and processed at various intervals from 1.6 minutes to 4 hours thereafter. Some rats were injected first with 35SO4 followed 5 minutes later by 0.3 mg of cycloheximide. This was done to terminate protein translation and allow events related to extracellular processing and degradation of the sulfated enamel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…These results raise the possibility that ameloblastin corresponds to the sulfated glycoprotein demonstrated by Smith et al (1995). However, experiments with glycosidases suggested that the majority of sulfate groups were attached to sugars that were connected to the protein via asparagine side-chains (N-linkages), resulting in the 65-kD sulfated glycoprotein (Smith et al 1995). Computer analysis of the ameloblastin cDNA sequence recognized no N-glycosylation target sites .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…These results raise the possibility that ameloblastin corresponds to the sulfated glycoprotein demonstrated by Smith et al (1995). However, experiments with glycosidases suggested that the majority of sulfate groups were attached to sugars that were connected to the protein via asparagine side-chains (N-linkages), resulting in the 65-kD sulfated glycoprotein (Smith et al 1995). Computer analysis of the ameloblastin cDNA sequence recognized no N-glycosylation target sites .…”
Section: Discussionmentioning
confidence: 95%
“…Matsuki et al (1995) constructed an unidirectional cDNA liberally from the growing end of the rat incisor, sequenced cDNA clones, classified their sequence, and showed that, among the enamel matrix-specific genes, the most redundant mRNAs next to amelogenin were for ameloblastin. These results raise the possibility that ameloblastin corresponds to the sulfated glycoprotein demonstrated by Smith et al (1995). However, experiments with glycosidases suggested that the majority of sulfate groups were attached to sugars that were connected to the protein via asparagine side-chains (N-linkages), resulting in the 65-kD sulfated glycoprotein (Smith et al 1995).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Dentine matrix contains both collagenous and non-collagenous proteins; the latter class also includes glycoproteins and phosphoproteins (6,(17)(18)(19)(20)(21). It has been shown that the sugar residues of the glycoconjugates are capable of inhibiting hydroxyapatite crystal formation (22)(23)(24).…”
mentioning
confidence: 99%